(untitled) (Journal of Human Sciences, 2022)
It is known that the Roman Empire reached its peak in the second century AD. But in the third century, it faced several crises that resulted in the emergence of the Byzantine state or the Eastern Roman Empire, namely political and economic instability, the raiding of Germanic tribes and Persians, in addition to the weakness of the pagan religion, and the accompanying deterioration in social systems and cultural institutions, which weakened, threatened and exposed the empire. for destruction. It can be said that the Byzantine Empire was born out of the crisis of the third century, which came as a result of the accumulation of problems that surfaced in that century, which necessitated changes and reforms that were a transitional period in which the accumulation of changes led to the beginning of a new era in human history. In those difficult times that the Roman Empire went through, Diocletian took the throne, who saved the empire from the brink of the abyss, and was able to fix the turmoil that the empire was suffering from, but his rule along with his partner soon collapsed, but those reforms were practical solutions to critical situations that require quick solutions Temporary, and the result was good in some cases. He restored security to most parts of the empire, and the borders were preserved for another century. After him, Constantine was able to restore order and enjoy a special place in history due to the actions he carried out, which had a clear impact in changing the face of history, and achieving the transition from the ancient world to the world of the Middle Ages, where this emperor took two steps of great importance: the first is his official recognition He became the first emperor to convert to Christianity, and the second he transferred the capital of the empire from ancient Rome to New Rome (Constantinople) and became the new capital of the Eastern Byzantine Empire.